KONSELING DALAM PERSPEKTIF ISLAM: INTEGRASI NILAI-NILAI ETIKA ISLAM DALAM PENYELESAIAN KONFLIK RUMAH TANGGA - Sylviah Sylviah (IAIN BONE, 2026)
This study aims to analyze the integration of Islamic ethical values into counseling as an approach to resolving marital conflicts. The research employs a normative literature study method by examining various sources related to Islamic counseling, Islamic ethics, and family conflict. The findings indicate that Islamic counseling serves not only as a psychological assistance process but also as a means of spiritual and moral guidance grounded in Islamic teachings. Ethical values such as honesty, trustworthiness, justice, patience, compassion, responsibility, and consultation (shūrā) constitute the primary principles in helping couples understand the roots of conflict, regulate emotions, improve communication, and reach fair and constructive solutions. The integration of these values makes Islamic counseling more comprehensive, as it focuses not only on conflict resolution but also on fostering harmonious and sustainable family relationships. Therefore, Islamic counseling plays a strategic role in strengthening family resilience and promoting household harmony.